Corruption and FDI in OIC Countries - Ahmad Jafari Samimi (Information Management and Business Review, 2011)
The purpose of the present paper is to investigate the impact of corruption on foreign direct investment revenues in OIC countries. To do so, we have concentrated on a sample of 16 countries for which the necessary data were available for the period 2002-2008. We have used panel regression analysis. Our empirical results support that openness and Gross domestic product (GDP) have positive impact and inflation and corruption have negative impact on FDI in OIC countries.